Animal Studies on Medicinal Herbs: Predictability, Dose Conversion and Potential Value. (4th April 2013) - Wojcikowski, Ken; Gobe, Glenda
<x xml:space="preserve">Abstract</x> Animal studies testing medicinal herbs are often misinterpreted by both translational researchers and clinicians due to a lack of information regarding their predictability, human dose equivalent and potential value. The most common mistake is to design or translate an animal study on a milligram per kilogram basis. This can lead to underestimation of the toxicity and/or overestimation of the amount needed for human therapy. Instead, allometric scaling, which involves body surface area, should be used. While the differences in the pharmacokinetic and pharmacodynamic phases between species will inevitably lead to some degree of error in extrapolation of results regardless of the conversion method used, correct design and interpretation of animal studies can provide information that is not able to be provided by in vitro studies, computer modeling or even traditional use. Copyright © 2013 John Wiley & Sons, Ltd.